A social realist account of the tutorial system at the University of Johannesburg - Layton, Delia Melanie (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2013)
Using Margaret Archer's social realist methodology, this study critically examines the construction of the tutorial system in several departments and faculties at the Auckland Park campus of the University of Johannesburg. The purpose of the study is to investigate the extent to which tutorials support the acquisition of programme and disciplinary epistemologies. Social realism calls for analytical dualism of 'the people' (agents) from 'the parts' (structure and culture). This requires the separate consideration of structures (social systems, rules, roles, practices, policies, institutions, and organisational structures like committees, units, departments, faculties), culture (ideologies, theories, beliefs and values as evidenced in discourses), and agency (people and their ability to act within and upon their own world in terms of their social roles and positions dependent on their ability to activate their emergent properties and powers). Through this investigation, an understanding was gained into how the emergent properties and powers contained within the material, ideational and agential elements helped to generate certain events and practices in the tutorial system. These generative mechanisms were examined to explore whether they enabled or constrained the construction of the tutorial system to provide epistemological access. The study shows that while many official policy documents construct the tutorial system as being an intervention to support academic success, particularly for first-years, there are some tensions within the document discourses, where, on the one hand, student success is constructed in terms of throughput numbers, or, on the other hand, as being about becoming a particular kind of person who is able to access and add to powerful knowledge. Furthermore, the study found that policies are not being consistently implemented. While certain key agents and actors, in the form of management, academics and tutors, were found to be able to overcome constraints and introduce innovative ways of enhancing access to target epistemologies, there is a need for consideration of structural and cultural constraints. For example, structures in the form of funding, venues and timetabling were found to constrain the tutorial system as did some of the discourses in the cultural domain: for example, in the form of certain dominant discourses around teaching and learning, beliefs about the purpose of the tutorial and the relationship between academics and the tutorial system. The study also found that the ontological aspects of 'learning to be' were not fore-grounded to any great extent in the ways in which the tutorial system was constructed. There needs to be more consideration of the ontological as well as the epistemological aspects of first-year study so as to take cognisance of the different learning needs of an increasingly diverse student body and to encourage the development of the student agency necessary for a deep engagement with the disciplinary epistemologies.
Keywords: University of Johannesburg; Education, Higher -- South Africa; Tutors and tutoring -- South Africa; College teaching -- South Africa; Archer, Margaret Scotford; College student development programs -- South Africa; Social realism; Tutorial system